The influence of social network in moderating the relationship between training transfer determinants and goal setting of Malay women owners of small businesses / Norlina Mohamed Noor - Mohamed Noor, Norlina (2014)
The main objective of this research is to investigate the moderating effect of social network in terms of the interaction between trainees and primary stakeholders to establish its influence on training transfer determinants and Malay women owners of small businesses' goal setting. The majority of the studies on training transfer have focused on the individual and situational factors in contributing towards training transfer but a very small number concentrated on the role of social network especially among Malay women owners of small businesses. The instrument used for this research is a modification of Training Transfer Model by Baldwin and Ford (1988) and Model of Excellence by McLagan and Bedrick (1983). Three factors: training content, training delivery and opportunity to use as training transfer determinants were taken from the Model of Training Transfer and trainer competency, which was taken from Model of Excellence, formed the conceptual framework for this research. Social network as moderating variable was added in this framework. Interaction of Social Network before, during, after and four months after training between trainees with organizer, trainer and colleagues were included as part of the items asked in the questionnaire. Women attending basic training programs organized by INSKEN (National Institute of Entrepreneurs), MARA (Council of Trust for Bumiputera) and JPW (Department of Women Development) were selected as the respondents for this research. Multiple and hierarchical regressions were used to analyze the data. The findings have confirmed that the interactions between the trainees that exist in the network structure do play a very important role in enhancing training transfer and helping trainees to achieve their goal setting.